2022
DOI: 10.18632/aging.204018
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA circ_0000423 regulates cartilage ECM synthesis via circ_0000423/miRNA-27b-3p/MMP-13 axis in osteoarthritis

Abstract: Circular RNA (circRNA) is related to many human diseases including osteoarthritis (OA). Our research purpose was to show that functional circRNAs have a role in the pathogenesis of OA, while also identifying potential circRNA that bind to miRNA-27b-3p. Microarray analysis was used to evaluate the expression of CircRNA in OA and normal cartilage. The role and functional mechanism of Circ_0000423 up-regulation were detected in OA and verified in vitro and in vivo . R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Multiple studies have found that circRNAs play an important role in OA. For example, circ_0000423 regulates cartilage ECM synthesis through the miRNA-27b-3p/MMP-13 axis 29 . TGF-β1 regulates chondrocyte proliferation and extracellular matrix synthesis in osteoarthritis through the circPhf21a-Vegfa axis 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have found that circRNAs play an important role in OA. For example, circ_0000423 regulates cartilage ECM synthesis through the miRNA-27b-3p/MMP-13 axis 29 . TGF-β1 regulates chondrocyte proliferation and extracellular matrix synthesis in osteoarthritis through the circPhf21a-Vegfa axis 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, 119 upregulated and 136 downregulated circRNAs were identified by RNA-seq in an OA mouse model induced by IL-1β [ 133 ]. A total of 11 downregulated and 101 upregulated circRNAs were identified in OA cartilage [ 134 ]. These changes in circRNA expression patterns indicate a potential function in OA.…”
Section: Ncrnas Involved In Cartilage Homeostasis and Oamentioning
confidence: 99%
“…CircADAMTS6/miR-324-5p/PIK3R3 axis participate in IL-1β-induced human chondrocyte dysfunction via the PI3K/AKT/mTOR signaling pathway [ 146 ]. Besides, the circ_0000423/miR-27b-3p/MMP-13 axis can affect the pathogenesis of OA [ 134 ]. Nevertheless, further research on the relationship between circRNAs and OA is required.…”
Section: Ncrnas Involved In Cartilage Homeostasis and Oamentioning
confidence: 99%
“…Over the last few decades, the function of circRNAs has become one of the most discussed issues, and circRNAs have been investigated as novel biomarkers of multiple diseases. Accumulated evidence indicates that circRNAs function as a sponge for the miRNAs involved in post-transcriptional regulation in OA ( 29 ). A recent study investigated the circRNA profiles in the osteoarthritic synovium and found that the hsa_circ_0072697–hsa_miR-6736–5p-LEP/ULK1 axis plays a role in cell senescence regulation ( 30 ).…”
Section: Discussionmentioning
confidence: 99%